2018
DOI: 10.1007/s00709-018-1207-3
|View full text |Cite
|
Sign up to set email alerts
|

A new Em-like protein from Lactuca sativa, LsEm1, enhances drought and salt stress tolerance in Escherichia coli and rice

Abstract: Late embryogenesis abundant (LEA) proteins are closely related to abiotic stress tolerance of plants. In the present study, we identified a novel Em-like gene from lettuce, termed LsEm1, which could be classified into group 1 LEA proteins, and shared high homology with Cynara cardunculus Em protein. The LsEm1 protein contained three different 20-mer conserved elements (C-element, N-element, and M-element) in the C-termini, N-termini, and middle-region, respectively. The LsEm1 mRNAs were accumulated in all exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 63 publications
2
6
0
Order By: Relevance
“…Most of the BnaLEA genes (78/148) were highly expressed in mature seeds and lowly expressed in other tested tissues (Fig. 2), which is consistent with the characterization of LEA genes that accumulate in large amounts during the late stage of seed development [40]. Unexpectedly, most of the LEA_2, LEA_3 and DHN subgroup members, as well as BnaLEA39 and BnaLEA40 from LEA_6, were highly expressed across different vegetative and reproductive organs during different development stages (Fig.…”
Section: Expression Pro Ling Of the Bnalea Genes In Different Tissues...supporting
confidence: 84%
See 2 more Smart Citations
“…Most of the BnaLEA genes (78/148) were highly expressed in mature seeds and lowly expressed in other tested tissues (Fig. 2), which is consistent with the characterization of LEA genes that accumulate in large amounts during the late stage of seed development [40]. Unexpectedly, most of the LEA_2, LEA_3 and DHN subgroup members, as well as BnaLEA39 and BnaLEA40 from LEA_6, were highly expressed across different vegetative and reproductive organs during different development stages (Fig.…”
Section: Expression Pro Ling Of the Bnalea Genes In Different Tissues...supporting
confidence: 84%
“…Correspondingly, the promoter sequences of LEA_6 members were rich in light-responsive and defense hormone-responsive cis-regulatory elements, and LEA_6 members were induced by abiotic stress and hormones-treatments (Table S2 and Figure S3). Typical LEA genes were exhibited high expression levels in the late stages of seed development in Arabidopsis [44] and rice [40], Similarly, we found that most of the BnaLEA gene family members are also highly expressed in the late stage of seed development (Table S3 and Fig. 2).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…It is worth mentioning that LEA protein (HORVU1Hr1G059900.1, HOR-VU3Hr1G030650.1) was also identified in GN18, but the upregulated expression fold change was less than that of GN2 ( Table S2 ). Early methionine (Em) protein, characterized as group 1 LEA protein, was first identified and described in wheat embryos and is reported to play a fundamental role in the response to environmental stress [ 64 , 65 ]. Em protein CS41, which is significantly expressed in barley seeds after 24 h and 48 h of salt stress, can respond to ABA [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to low-temperature damage, the plants also experience drought and salt stress during seed germination and seedling growth. Considering the harsh growth environment of L. apetalum, late embryogenesis abundant (LEA) proteins have recently been investigated; LEA family proteins play an important role in abiotic stress tolerance in plants, including cold, drought, and salt stresses (Xiang et al 2018).…”
Section: Introductionmentioning
confidence: 99%